Inter-Rater Reliability of the Feline Grimace Scale in Cats Undergoing Dental Extractions - Watanabe, Ryota; Doodnaught, Graeme M.; Evangelista, Marina C.; Monteiro, Beatriz P.; Ruel, Hélène L. M.; Steagall, Paulo V. (Frontiers in Veterinary Science, 2020)
This study aimed to evaluate the inter-rater reliability of the Feline Grimace Scale (FGS) in cats undergoing dental extractions and the effects of the caregiver’s presence on the FGS scores. Twenty-four cats (6 ± 3.3 years old; 4.9 ± 1.7 kg) undergoing oral treatment were included in a prospective, blinded, randomized, clinical study. They underwent treatment under general anesthesia (acepromazine-hydromorphone-propofol-isoflurane-meloxicam-local anesthetic blocks) at day 1 and were discharged at day 6. Images of cat faces were captured from video recordings with or without the caregiver’s presence at 6 hours postoperatively (day 1), day 6, and before and after rescue analgesia. Images were randomized and independently evaluated by four raters using the FGS [five action units (AU): ear position, orbital tightening, muzzle tension, whiskers change and head position; score 0-2 for each]. Inter-rater reliability and the effects of the caregiver’s presence were analyzed with intraclass correlation coefficient [single measures (95% confidence interval)] and the Wilcoxon signed-rank test, respectively (p < 0.05). A total of 91 images were scored. Total FGS scores showed good inter-rater reliability [0.84 (0.77-0.89)]. Reliability for each AU was: ears [0.68 (0.55 - 0.78)], orbital tightening [0.76 (0.65 - 0.84)], muzzle [0.56 (0.43 - 0.69)], whiskers [0.64 (0.50 - 0.76)] and head position [0.74 (0.63 - 0.82)]. The FGS scores were not different with [0.075 (0-0.325)] or without [0.088 (0-0.525)] the caregivers’ presence (p = 0.12). The FGS is a reliable tool for pain assessment in cats undergoing dental extractions. The caregiver’s presence did not affect FGS scores.